Patterns of sensory loss following fractional posterior fossa Vth nerve section for trigeminal neuralgia. Issue 9 (September 1982) - Hussein, M; Wilson, L A; Illingworth, R
Abstract : Twenty-five patients with trigeminal neuralgia have been treated by fractional posterior fossa Vth nerve section. The procedure is shown to be effective in relieving pain, preserving corneal sensation and the motor root. Nineteen patients showed little loss of light touch sensation, and in 15 of these there was dissociation of sensory loss to pinprick and light touch. The results support the concept that there is some anatomical separation of fibres subserving light touch and pain in the posterior root of the nerve.